Mekanisme GCG dan leverage terhadap manajemen laba pada sektor manufaktur - Hildah Hildah; Santi Retno Sari (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2018)
This study aims to provide empirical evidence regarding the effect of Good Corporate Governance and Leverage on Earnings Management. The object of this research is Manufacturing companies registered in IDX for the period 2012-2016 using purposive sampling techniques in data collection. Testing the hypothesis of the study using panel data regression analysis techniques with E-Views 8. The findings in this study that all variables can have a direct effect on earnings management. Also, the Audit Committee, the Board of Directors and Leverage cannot influence earnings management, while the Independent Commissioner has a significant effect on earnings management. Practical implications can be found in this article.